Grass huts and warehouses : Pacific beach communities of the nineteenth century - Ralston, Caroline (Pacific studies series., 2014)
A pioneering study of early trade and beach communities in the Pacific Islands and first published in 1977, this book provides historians with an ambitious survey of early European-Polynesian contact, an analysis of how early trade developed along with the beachcomber community, and a detailed reconstruction of development of the early Pacific port towns. Set mainly in the first half of the 19th century, continuing in some cases for a few decades more, the book covers five ports: Kororareka (now Russell, in New Zealand), Levuka (Fiji), Apia (Samoa), Papeete (Tahiti) and Honolulu (Hawai'i).